Recent advances in HemN-like radical S-adenosyl-l-methionine enzyme-catalyzed reactions. Issue 1 (10th July 2019) - Jin, Wen-Bing; Wu, Sheng; Xu, Yi-Fan; Yuan, Hua; Tang, Gong-Li
Abstract : HemN-like radical S -adenosyl-l -methionine (SAM) enzymes have been recently disclosed to catalyze diverse chemically challenging reactions from primary to secondary metabolic pathways. Abstract : Covering: 2012 to 2019 HemN-like radical S -adenosyl-l -methionine (SAM) enzymes have been recently disclosed to catalyze diverse chemically challenging reactions from primary to secondary metabolic pathways. In this highlight, we summarize the reaction examples catalyzed by HemN-like enzymes to date and the enzymatic mechanisms reported. From the recent mechanistic investigations, we reason that there is a shared initiating mechanism wherein a characteristic SAM methylene radical is proposed to abstract a hydrogen atom from an sp 3 carbon or add onto an sp 2 carbon center although variations occur thereafter from reaction to reaction, as well as providing a brief insight into some future prospects.